Education Quality Improvement Through the Development of Hilda Taba's Curriculum - Osmi Zein R; Yurni Suasti; Ernawati Ernawati (International Journal of Educational Dynamics, 2021)
To develop a curriculum, many people will be involved, starting from teachers who are the spearheads in the field to experts who determine the direction of education policy. Hilda Taba an education expert makes a curriculum development that is different from other experts, Hilda Taba develops by developing an inductive model, namely from the bottom (bottom-up), teachers must start the process by creating a special teaching and learning unit for their students at school and not involved in the design of a general curriculum. Therefore Taba adopts an inductive approach that starts with the specifics and builds into a general design. According to him, curriculum development that encourages teacher innovation and creativity is inductive, which is the opposite of the traditional model. The steps in the curriculum development process according to Taba are Step 1: Needs diagnosis, Step 2: formulation of the main points, Step 3: Content selection, Step 4: Organization of content, Step 5: Selection of learning experiences, Step 6: Organization of learning experiences, Step 7: determining what to evaluate and how to do it. By implementing the steps that have been prepared by Hilda Taba.